Effectiveness of Cinnamon (Cinnamomum burmannii) Ethanol Extract Against Staphylococcus aureus Growth - Nurul Huda; Ratih Dewi Dwiyanti; Anny Thuraidah (Tropical Health and Medical Research, 2019)
Cinnamon (Cinnamomum burmannii) is widely used by the public as a food ingredient and contains chemical compounds such as alkaloids, flavonoids, polyphenols, saponins, and terpenoids which function as an antibacterial against Staphylococcus aureus. This study aims to determine the Minimum Inhibitory Concentration and Minimum Bactericidal Concentration of cinnamon ethanol extract on Staphyloccocus aureus. This research is experimental with posttest only control group design through the tube dilution method. The results of the Minimum Inhibitory Concentration (MIC) study showed no clarity at concentrations of 30% and 40%. The results of the Minimum Bactericidal Concentration (MBC) obtained the number of colonies at a level of 10% by 51 CFU / plate, 20% by 27 CFU / plate, 30% by 6 CFU / plate and 40% by 0 CFU / plate. Based on the results of this study concluded that MIC cinnamon ethanol extract was 30%, and MBC cinnamon ethanol extract was 40%.